ART THERAPY METHODS IN SOCIAL SUPPORT FOR CHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN UBEKISTAN - Alexandra Yadgarova (The Conference Hub, 2025)
The article pays special attention to the relevance of the problem of preserving, developing and strengthening the mental health of children with disabilities. The method of isotherapy is revealed – therapy by means of art, this method is aimed at the effective socialization of children with disabilities, as it enables children to solve their inner experiences, difficulties, allows them to feel full, in demand for society.
Keywords: art therapy, method, art therapy techniques, socialization, children with special educational needs.